Comparison of the Delay in Processing Time and Protective Plastic Cases in Two Phosphor Plate Systems - Ali Murat Aktan; Mehmet Ertuğrul Çiftçi; Faruk Akgünlü (The Scientific World Journal)
Objective. The purpose of this study was to analyze two phosphor plate systems (PSPs) (Dürr Dental, Digora Optime) according to their scanning delay and protective plastic case performances. Methods. Two PSPs using an aluminum step wedge were exposed. These plates were placed in three different protective plastic cases (manufacturers' original cases, black case, and white case) before obtaining the radiographs and were then processed immediately and 1, 5, 10, 30, 60, 120, 240, and 480 min after exposure. Mean gray values (MGVs) of the 3rd, 5th, 7th, and 9th steps of the wedges were compared using ANOVA. Results. Statistically significant differences were found between the two PSPs (). ANOVA revealed that the MGVs of four steps of the wedges were significantly different from each other for all scan delays (). MGVs increased with increasing scanning delay, except the group with Dürr plates in their original cases. Reduction in image quality began 5 min after exposure in the other Dürr plate groups. Conclusions. Within the limitations of the current study, it can be concluded that scanning delay causes a reduction in image quality, and using the manufacturer's original protective case will result in better performance of PSPs.